Model of cyberspace threat early warning based on cross-domain and collaboration - Gang XIONG; Yuwei GE; Yanjie CHU; Weiquan CAO (网络与信息安全学报)
The development of network threat shows the characteristics of initiative,concealment and ubiquity.It poses a severe challenge to the passive,local and isolated traditional network defense mode.In view of the new trend of integration of big data，artificial intelligence and network security,a cross-domain collaborative network threat early warning model was proposed,which could enable and increase efficiency for cyberspace security.Firstly,starting from the overall structure of the protected network space,the model constructs a cross-domain function framework with the vertical and horizontal conjunction by dividing the security threat domain,decomposing the system function,designing the information sharing mechanism.Secondly,to enhance the ability of threat information detection,the collaborative technology architecture is designed by the logic of hierarchical management,and the key technologies involved in threat information perception,processing and application,are systematically introduced.Finally,with the help of application scenarios,qualitatively the capability increment of the proposed threat early warning model was described.